SPEECH ACT BEHAVIOR OF GENERATION Z TIKTOK USERS IN COMMUNICATION WITH PARENTS IN PEMATANG GAJING VILLAGE SIMALUNGUN - Dwi Arlintang; Fakhrur Rozi (Program Pascasarjana UIN Sumatera Utara, 2026)
This study examines the speech act behavior of Generation Z TikTok users in communication with their parents in Pematang Gajing Village, Simalungun Regency. The increasing use of TikTok among Indonesian Gen Z has encouraged the transfer of slang expressions, body gestures, and facial expressions from digital content into everyday face-to-face interaction, including within family communication. This research employs a descriptive qualitative approach using in-depth interviews and observation involving six Gen Z informants and six parents as supporting informants. Data were analysed using Austin and Searle’s speech act theory through the dimensions of locution, illocution, and perlocution. The findings reveal three patterns of intergenerational communication dynamics: semantic gaps that trigger conflict, positive adaptation that strengthens relationships, and violations of relational norms that lead to serious tension. The novelty of this study lies in its focus on rural intergenerational communication within a strong traditional cultural setting, showing that the transfer of TikTok-mediated communication styles does not merely create linguistic shifts but also reconfigures family relational norms. This study contributes to pragmatic and sociolinguistic scholarship by demonstrating that parental openness is a key variable in determining whether digital speech patterns produce conflict or relational adaptation in family communication.